miR-302d Competitively Binding with the lncRNA-341 Targets TLE4 in the Process of SSC Generation - Yani Zhang; Wenhui Zhang; Cai Hu; Yingjie Wang; Man Wang; Qisheng Zuo; Ahmed Kamel Elsayed; Yi Li; Bichun Li (Hindawi Limited, 2021)
MicroRNAs (miRNAs) are essential factors in the reproductive process of poultry. Here, we found miR-302d is a potential differentiation and negative factor of chicken embryonic stem cells (ESCs) into spermatogonia stem cells (SSCs). The competition mechanism was carried out for the preliminary exploration to determine the relationship among miR-302d, lncRNA-341(interacting with miR-302d), and target gene TLE4. The results showed that lncRNA-341 can competitively bind to miR-302d to decrease the targeted binding of miR-302d and TLE4 which promotes the differentiation of chicken SSCs. Moreover, it is suggested that miR-302d may participate in the Wnt signaling pathway through TLE4.